Determination of Optimum Rate of Nitrogen, Phosphorus, Potassium and Boron for Leaf and Seed Yield of Lettuce (Bangladesh Journal of Agricultural Research, 2022)
The experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, during October 2012 to May 2013 to determine the optimum rate of nutrients for sustainable lettuce production. Nineteen treatment combinations were considered with five levels of each elements such as nitrogen viz. 0, 50, 100, 150 and 200 kg ha-1; phosphorus viz. 0, 25, 50, 75 and 100 kg ha-1; potassium viz. 0, 50, 100, 150 and 200 kg ha- 1; boron viz. 0, 0.5, 1.0, 1.5 and 2.0 kg ha-1. Results revealed that treatment T3 (N100P50K100B1.0) showed the maximum leaf and seed yield of lettuce. Fertilizer doses under T3 also showed the highest gross margin Tk. 305825 and Tk. 2816675 ha-1 and BCR 7.50 and 70.0 for leaf and seed yield, respectively. But, from regression analysis optimum doses of nitrogen, phosphorus, potassium and boron for maximum leaf yield (23.11 ton ha-1) and seed yield (571.5 kg ha-1) were N143P74K95B1.26 and N136.4P67.8K118.0B1.0, respectively that could be recommended as the best combination of nutrients for achieving higher leaf and seed yield of lettuce.Bangladesh J. Agril. Res. 45(4): 455-471, December 2020